Media and Information Technology in Ten Years’ Time: A Society of Control Both from Above and Below, and From Outside and Inside - Jörg Becker (tripleC: Communication, Capitalism & Critique, 2015)
In the process of continual change from the hand axe to the factory and now to industrial production 4.0, technology has had, and still has, two basically invariable functions: control and rationalisation. Each of these two terms is to be understood in a very comprehensive sense, in technical, engineering, commercial, legal and also social terms. This tenet also applies to television and to information technology. In my lecture, the terms “above” and “below” stand for a model of social stratification; they stand for capital and labour. The terms “outside” and “inside” stand for the external conditions of the class struggle from “above” and “below”. The external conditions mean the social and the inside conditions mean the psychological environment. Both television and information technology rely on content and organisational forms that run from above to below (from top to bottom). Moreover, contrary to Gutenberg’s invention of moving letters, today innovations in the media and IT fields no longer run from the bottom up, but only from the top down. While television conditions the individual from outside, users of social media internalise that same conditioning as a liberation from constraints.